STUDIES ON THE RELATIONSHIPS BETWEEN STANDARD LENGTH AND WHOLE RETINA OF THREE FRESHWATER FISHES TER FISHES - RAVIKANT KUMAR SAURABH,; KRISHAN NANDAN PD. SINGH, (The Bioscan, 2009)
A comparative evaluation between different standard length (SL) and whole retina (WR) in three fresh water air breathing fishes namely A. cuchia, C. fasciatus and C. batrachus was done. A negative allometric relationship between two parameters was established in A. cuchia and C. fasciatus but in C. batrachus a positive correlation was observed. However, after attains a critical point of growth, the growth of retina in C. batrachus was of retina stopped and thereafter differential growth in SL and WR of the fish were observed.